CONSUMERISEM REPRESENTED IN INSTAGRAM CAPTIONS OF @BLPBEAUTY PRODUCT - Utami, Okthi Raihan; Budiwati, Tri Rina (Universitas Negeri Malang, 2023)
This study aims to analyze textual features, discursive practices, and social practices based on the Fairclough three-dimensional model contained in beauty product captions on Instagram @blpbeauty to attract customer attention.This research is descriptive qualitative method. To collect and anlyze the data, this study used observation and document techniques by Creswell and used domain analysis technique proposed by Suyitno. This research is also analyzed using a Critical Discourse Analysis with a three-dimensional model proposed by Fairclough. Based on the result, the researcher found that there are textual features such as overwording and rewording, metaphors, active sentences, positive sentences, negative sentences, declarative and imperative sentences, grammatical questions, simple sentences, compound and complex sentences, use of pronouns, and modality. Meanwhile, in discursive practice, the researcher found advertising discourse in the blpbeauty Instagram caption that could attract customer attention. Then at the stage of explanation (social practice), the writer finds consumerism in blpbeauty's Instagram caption.